DIVERSITY AND ABUNDANCE OF THE SPONGES OF THE LOWS OF SANCHO PARDO, ARCHIPIELAGO DE LOS COLORADOS, CUBA - de la Nuez Hernández, Daril (2011)
Twelve sampling stations were established with bathymetric profiles (5, 10 and 15 m) in five locations in Bajos de Sancho Pardo, Los Colorados Archipelago, north-western region of Cuba. A 1x1m square quadrant was used as a sampling unit, with 30 quadrants being sampled per station. Fifty species of sponges were identified belonging to class Demospongiae, distributed in 33 genera, 10 orders and 22 families. In the shallowest stations the prevailing species was Cliona aprica, while Aplysina cauliformis, A. fistularis f. insularis and Ircinia felix prevailed in the deeper stations. Species richness tended to increase with depth. The contamination index, which was calculated based on the abundance of sponges indicating this factor, was not high. Sponge density showed significant differences between stations; however, it was not particularly high in the region maybe due to the stress induced by strong waves during winter cold fronts and frequent,intense cyclones that affect the region.